2010
DOI: 10.1016/j.ijdevneu.2010.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of early malnutrition, isolation and seizures on memory and spatial learning in the developing rat

Abstract: Our findings show that undernourishment and seizures have an additive detrimental effect on body and brain weight as well as on spatial memory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 31 publications
4
32
0
Order By: Relevance
“…Another study about the effects of malnourishment and seizures on memory and spatial learning in a model of developing brain was carried out by Hemb and colleagues [33]. Malnourished groups were maintained on a starvation regimen from postnatal day 2 (P2) to postnatal day 15 (P15).…”
Section: Animal Studiesmentioning
confidence: 99%
“…Another study about the effects of malnourishment and seizures on memory and spatial learning in a model of developing brain was carried out by Hemb and colleagues [33]. Malnourished groups were maintained on a starvation regimen from postnatal day 2 (P2) to postnatal day 15 (P15).…”
Section: Animal Studiesmentioning
confidence: 99%
“…Agematched control rats remained with their dams (Crnic, 1980;Ladd et al, 1996;Nunes et al, 2000;Hemb et al, 2010;Florian and Nunes, 2010). The deprivation period was increased by 4 h for three consecutives days, from 2 h on P1 to 12 h on P4.…”
Section: Malnutrition Paradigmmentioning
confidence: 99%
“…When seizures appeared consecutively with no normal activities (grades IV–V), this was considered SE and indicated that the model was successfully induced. After SE had been established and pharmacological intervention was completed, spatial orientation and memory tests were conducted using an MWM (28). …”
Section: Methodsmentioning
confidence: 99%